Mining Controversy Based Study Assessing Sustainable Development and Eco-Tourism to Save Ecology - Sonbay, Ermalindus Albinus Joseph (Jurnal Pendidikan dan Kebudayaan Missio, 2016)
Mining in NTT are controversial because they involve manipulation and engineering ofinterest surrounding the hegemony of mineral and natural products. Welfare of the people which is usedas a propaganda tool precisely wrap beautifully personal benefit of the mining entrepreneur and also theregional administration directly into the shade and the rest of the law and politics of the local entrepreneurs.Mining is not just the affairs of the government and the mining corporations, especially the exclusivecommunity of mining entrepreneurs. Mining requires a dialectic of ideas, the way, the pattern to therehabilitation of nature that combines holistic and absolute, all stakeholders (stakeholders), all owners ofinvestment and capital (shareholders) and most important of all the people who support the area around,that during all this time to enjoy and meet the daily needs of nature. Forgetting one of the elements isletting the conspiracy that destroys this vision together. Integrative cooperation, open and trustworthy issomething that is necessary in this dialectic. Because, only with this cooperation the transfer of technologyand knowledge that can humanize and ensuring environmental sustainability can occur.Keywords: mining, construction, tourism, ecology